#### Answer

The solution set is $\left\{-12, 1\right\}$.

#### Work Step by Step

Add $-12$ to both sides of the equation to obtain:
$x^2+11x-12=0$
Factor the trinomial by looking for the factors of $-12$ whose sum is equal to the coefficient of the middle term ($11$).
These factors are $-1$ and $12$. This means that the factored form of the trinomial is $(x-1)(x+12)$.
Thus,
$x^2+11x-12=0
\\(x-1)(x+12)=0$
Equate each factor to 0; then, solve each equation to obtain:
$x-1=0 \text{ or } x+12=0
\\x=1 \text{ or } x=-12$
The solution set is $\left\{-12, 1\right\}$.